ANALISIS EFEKTIVITAS PENERAPAN STRATEGI SPONSORSHIP DALAM MENINGKATKAN MINAT BELI ULANG STUDI KASUS UMKM CV. JOGJA KONVEKSI - Laura Amelia Triani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Repurchase intention is one of consumer loyalty measurement. Meanwhile sponsorship is becoming an increasingly popular marketing communication nowadays. Many previous studies have looked at repurchase intention based on other factors. So the purpose of this study is to provide analysis and recommendations to companies on the results of implementing the Sponsorship strategy in increasing repurchase intention. This study also take a look how the flow of strategy can make a positive influence on company recognition. A qualitative approach with descriptive analysis is used based on data collection through sales data, consumer data, interviews, observations and experiments on 5 sponsorship implementations in CV. Jogja Konveksi. The results of this study indicate an increase in repurchasing intention in the product made by this company. Based on consumer data, it also shows the increase of recall purchases and transactions at CV. Jogja Konveksi.